2017
DOI: 10.1002/anie.201611567
|View full text |Cite
|
Sign up to set email alerts
|

Automated Synthesis of Well‐Defined Polymers and Biohybrids by Atom Transfer Radical Polymerization Using a DNA Synthesizer

Abstract: A DNA synthesizer was successfully employed for preparation of well-defined polymers by atom-transfer radical polymerization (ATRP), in a technique termed AutoATRP. This method provides well-defined homopolymers, diblock copolymers, and biohybrids under automated photomediated ATRP conditions. PhotoATRP was selected over other ATRP methods because of mild reaction conditions, ambient temperature, tolerance to oxygen, and no need to introduce reducing agents or radical initiators. Both acrylate and methacrylate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(72 citation statements)
references
References 80 publications
0
72
0
Order By: Relevance
“…Many studies have shown that the multivalent presentation of ligands to soluble proteins and cell receptors is highly dependent on ligand density,spacing, and orientation. [6][7][8][9][10][11][12] There has therefore been growing interest in methods that will enable the high throughput synthesis and screening of well-defined polymers.Early works showed the possibility of using automatic synthesisers to conduct conventional controlled radical polymerisations (CRPs) in inert atmospheres, [13][14][15][16][17] but the recent development of various oxygen tolerant CRP mechanisms including singlet oxygen trapping, [18][19][20][21][22][23] enzyme degassing, [24][25][26][27][28][29] among others, [14,[30][31][32][33] have now been applied to the synthesis of polymer libraries in low volumes and open to the atmosphere. [34][35][36][37][38][39] These techniques have been used to prepare polymers with complex architectures such as arm first stars, [36,37] and block copolymers, [39] and have been applied to the investigation of polymerisationinduced self-assembly (PISA) systems.…”
mentioning
confidence: 99%
“…Many studies have shown that the multivalent presentation of ligands to soluble proteins and cell receptors is highly dependent on ligand density,spacing, and orientation. [6][7][8][9][10][11][12] There has therefore been growing interest in methods that will enable the high throughput synthesis and screening of well-defined polymers.Early works showed the possibility of using automatic synthesisers to conduct conventional controlled radical polymerisations (CRPs) in inert atmospheres, [13][14][15][16][17] but the recent development of various oxygen tolerant CRP mechanisms including singlet oxygen trapping, [18][19][20][21][22][23] enzyme degassing, [24][25][26][27][28][29] among others, [14,[30][31][32][33] have now been applied to the synthesis of polymer libraries in low volumes and open to the atmosphere. [34][35][36][37][38][39] These techniques have been used to prepare polymers with complex architectures such as arm first stars, [36,37] and block copolymers, [39] and have been applied to the investigation of polymerisationinduced self-assembly (PISA) systems.…”
mentioning
confidence: 99%
“…Similarly, Matyjaszewski's group demonstrated that an optical fibre UV source can be used for the oxygen-tolerant photoATRP of (meth)acrylates. [24] Poly et al demonstrated that complex of CuBr 2 with 1,10-phenanthroline as ligand can be employed in the mediation of the photoATRP of MMA in the presence of oxygen under high-intensity blue LED light. [25] Although various polymerization techniques have been used for the polymerization of MBL, there was no report on conducting a reversible deactivation radical polymerization of MBL using low concentration of catalyst in the presence of oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…[2,7,17] Theinitial homolytic substitution (S H 2) between triethylborane and oxygen molecule provided ethyl radical (EtC)and boryl peroxyl radical (BOOC). Thefirst oxidized boron adduct could be cleaved and rearranged to EtB(OEt) 2 ,a nd finally formed B(OEt) 3 .T hree key boron intermediates were all detected by 11 BNMR spectroscopy (Supporting Information, Figure S10). Thee thylperoxy radical was involved in another S H 2 reaction with triethylborane to form active ethyl radical and corresponding oxidized boron product Et 2 B(OOEt).…”
mentioning
confidence: 99%
“…The freeze-pump-thaw technique and deoxygenation with inert gas are widely used but time-consuming methods to remove oxygen. Several methods with some degree of oxygen tolerance were developed via consuming oxygen by excess radicals or converting oxygen to non-initiating species, including photoinduced atom-transfer radical polymerization (photoATRP), [3] photoinduced electron/energy-transferreversible addition-fragmentation chain-transfer (PET-RAFT). [4] Glucose oxidase (GOx) was capable of converting oxygen with d-glucose into hydrogen peroxide;t herefore,i tw as elegantly adopted as oxygen scavenger in RAFT [5] and ATRP under ambient atmosphere.…”
mentioning
confidence: 99%
See 1 more Smart Citation